Perbedaan Kemandirian Antara Anak Sulung dan Anak Bungsu di Say Paku Kecamatan Kinali - Putri, Titin; Yusri, Fadhilla; Rahmi, Alfi (Indonesian Research Journal on Education, 2023)
The low independence of students in learning is an activity that can be observed in learning. This is shown from the 10 eldest and youngest children that the writer observed, there were only 4 eldest children who did not do their own work, but sometimes asked others for help to take something, and the 6 youngest children who always did something always asked for help, and did not can do, both small and big things, meaning in terms of eating, ask for help to be taken by siblings or parents, and it is difficult to do something without encouragement from others. This type of research is a comparative descriptive study that aims to determine the differences in the independence of the eldest and youngest children. The research design used cross sectional (cross-sectional) because the research data (independent variable and dependent variable) were measured at the same time or for a moment. Based on the data processing used, this research is classified as quantitative research. The population in this study is the eldest child, and the youngest child in Say Paku, Kinali District, amounting to 112. The eldest child is 55 people, and the youngest child is 57 people. The data collection technique used is through recapitulation of independence questionnaires. The data analysis technique uses an independentsample T-test, but before testing the hypothesis, the requirements for analysis are tested for normality and homogeneity tests. Based on the results of hypothesis testing, the results of the tcount value of 6.111 at a significant level of 0.000 compared to the value in the t table with df = 110 located at the t-table value = 1.66 then the magnitude of the tcount value > ttable (6.111 > 1.66) can be seen Ha is accepted and Ho is rejected. So it can be concluded that there is a difference in the influence of the independence of the eldest child and the youngest child where the eldest child is more independent than the youngest child.